Pengabdian Masyarakat Melalui Program Berbagi Takjil - Erlina, Lira; Auliya, Khanna; Al Fudiah, Nurul; Shadiqah, Cut Aufia; Fadhillah, Salsabila; Rizki, Nurul Latifa Komala (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2024)
This research aims to discuss the phenomenon of sharing takjil during Ramadan in Indonesia. It is a qualitative study applying literature review method with maudhu'i hadith cultural perspective and phenomenological approach. The results and discussion cover the phenomenon of sharing takjil during Ramadan in Indonesia, the ma’anil hadith of sharing takjil during Ramadan, as well as the virtues and benefits of sharing takjil. The study concludes that the phenomenon of sharing takjil during Ramadan in Indonesian society has a positive impact on the recipients and carries many virtues and benefits for the givers in both human relations (hablumminannas) and relations with the Creator (hablumminallah).